PENYUSUNAN LAPORAN KEUANGAN UMKM BERDASARKAN SAK-EMKM (STUDI KASUS PADA CV. ALMARN LIGURBAR FARM) - Fitratunnisa, Puja; Putra, Hery Astika; Halpiah, Halpiah (Nusantara Hasana Journal, 2025)
Joper chicken farm SMEs face financial management challenges due to limited knowledge of accounting and unstructured recording. This study analyzes the application of SAK EMKM on CV. Almarn Ligurbar Farm to improve the quality of financial reporting. Using a case study with primary data from business owner interviews and secondary data of financial documents December 2023-June 2024. Qualitative descriptive data were analyzed by classifying transactions according to EMKM SAK to prepare financial statements. The results showed that SAK EMKM succeeded in converting simple cash records into structured reports that reflect actual conditions. CV. Almarn Ligurbar Farm recorded a net loss of Rp4, 739, 602 with total assets of Rp122, 578, 698, feed costs dominated 64% of operating expenses of Rp44, 921, 002. The implementation of the EMKM SAK enables the identification of sources of losses, increases transparency, and provides a foundation for strategic decision-making for livestock MSMEs.